Польський міф про "східні креси" в польсько-українських відносинах - Гальчак, Б. (Історичний архів. Наукові студії, 2013)
Проаналізовано міф «східні околиці», який існує в польській традиції. Цей міф є
расистським. Він спрямований проти українців, білорусів, литовців, росіян. Autor poddał analizie mit «Kresów Wschodnich», który istnieje w polskiej tradycji. Mit ten ma
charakter rasistowski. Jest skierowany przeciwko Ukraińcom, Białorusinom, Litwinom,
Rosjanom. After the fall of the communist system, in Polish publications of a journalistic and scientific
character became widespread to use the term «eastern borderlands»(«Kresy Wschodnie») for
the former lands of the II. Rzeczpospolita, which after World War II became part of the Soviet
Union. Nowadays they belong to Ukraine, Belarus and Lithuania. In Polish, the term was used
already in the 16th century.At that time, it was used for steppe region between Rzeczpospolita
and Crimean Khanate. During the II Rzeczpospolita (between the two world wars), the Polish
nationalists have used the term «eastern borderlands», to identify eastern territories of
multinational country. Moreover, Lviv was not considered as a part of «eastern borderlands»
during interwar period. Polish politicians, who sought an agreement with the Ukrainians,
avoided use of the term «eastern borderlands». The concept of «borderlands» appears not only
in Polish language. It comes from tradition of the colonial conquest. It means the transition area
between countries, without precisely marked border line. «Borderlands» is a wild country, with
no functioning government, police or judiciary. State authorities are represented only by the
military. Using the term «eastern borderlands» to describe the former eastern territories of the II
Rzeczpospolita is not true. On these areas border lines were precisely marked. State
administration, police and judiciary operated. In some cities (Vilnius, Lviv) there were
universities. The term «eastern borderlands» is offensive to the inhabitants of these lands:
Ukrainians, Belarusians, Lithuanians, Jews, but also Poles. Makes them savages, living in a
world of lawlessness and continuous struggle. However, use of the term «borderlands» is not
always associated with the actual occurrence of this phenomenon. This term also includes a
strong ideological content.It is a belief in the superiority of their race, conviction of right to hold
authority over the ethnically strangers. «Borderland Poles» (‘kresowiacy») are descendants of
foreign invaders, who have conquered the land using military. They are aware of being a
minority in society. However, believe that they have exclusive right to decide about fate of
«native» population, which they consider to be lower in terms of civilization. They want to make
a «symbolic annexation» of the country, which has already been conquered militarily. Using the
Polish term «eastern borderlands» is very offensive to Ukrainians. This term includes a huge
load of contempt and a sense of racial superiority, just as the term «anti-Semitism» against the
Jews. The dialogue between the «Borderland Pole» and Ukrainian is impossible, as a dialogue
between a Jew and anti-Semite. After World War II the term «anti-Semitism» has become
politically incorrect in Poland. «Eastern borderlands» are still «correct».